2014
DOI: 10.1002/brb3.220
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Met66 modulates the cumulative effect of psychosocial childhood adversities on major depression in adolescents

Abstract: BackgroundThe interplay among lifetime adversities and the genetic background has been previously examined on a variety of measures of depression; however, only few studies have focused on major depression disorder (MDD) in adolescence.MethodsUsing clinical data and DNA samples from mouthwash gathered from an epidemiological study on the prevalence of mental disorders in youths between 12 and 17 years old, we tested the statistical interaction between a set of psychosocial adversities experienced during childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
3
14
0
1
Order By: Relevance
“…We focused on adolescence because most previous G 9 E studies focused on depression were of adults, with earlier reviewed research suggesting that the interaction between BDNF gene and environment may vary across development (e.g., Casey et al 2009;Lenroot and Giedd 2011). Our findings, together with prior adolescent studies (Chen et al 2012;Cruz-Fuentes et al 2014;Gottfredson et al 2014), support the propostion that BDNF Val66Met 9 Environment might vary between adolescents and adults. Specifically, the Val version of BDNF appears to confer heightened susceptibility to environmental influences in the case of youth, whereas the Met version of BDNF operates in this manner with regard to depression and adversity in the case of adults (see meta-analysis in Hosang et al 2014).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We focused on adolescence because most previous G 9 E studies focused on depression were of adults, with earlier reviewed research suggesting that the interaction between BDNF gene and environment may vary across development (e.g., Casey et al 2009;Lenroot and Giedd 2011). Our findings, together with prior adolescent studies (Chen et al 2012;Cruz-Fuentes et al 2014;Gottfredson et al 2014), support the propostion that BDNF Val66Met 9 Environment might vary between adolescents and adults. Specifically, the Val version of BDNF appears to confer heightened susceptibility to environmental influences in the case of youth, whereas the Met version of BDNF operates in this manner with regard to depression and adversity in the case of adults (see meta-analysis in Hosang et al 2014).…”
Section: Discussionsupporting
confidence: 66%
“…Notably, though, a study of Chinese adolescents found that it was Val-BDNF carriers who proved most susceptible to depressive symptoms in the face of stressful life events (Chen et al 2012). Such results would seem to be in line with work with Mexican adolescents (12-17 years) showing BDNF Val/Val homozygotes to be most at risk of depression when facing cumulative psychosocial adversities (Cruz-Fuentes et al 2014), and with U.S. adolescents indicating that Val-BDNF carriers manifested the most depressive symptoms when victimized by their peers (Gottfredson et al 2014). Collectively, the work just cited points to potential developmental, cultural, and ethnic variation in how the BDNF Val66Met polymorphism interacts with the environment in predicting depression.…”
Section: Bdnf Val66met 3 Environment On Depressionsupporting
confidence: 61%
“…Full-length articles of screening studies, studies in non-adolescents or with a mixed sample with the age beyond the range of 10–19 years for adolescents or 20–25 years for young adults, studies with only the mean age, studies without clearly identified gene expression or polymorphism, or others was excluded from the analysis. Finally, 47 full-length articles (Eley et al, 2004 ; Mamalakis et al, 2004 ; Burcescu et al, 2005 ; Miraglia del Giudice et al, 2006 ; Sjöberg et al, 2006 ; Geng et al, 2007 ; Hilt et al, 2007 ; Pandey et al, 2007 , 2012 ; Feng et al, 2008 ; Aslund et al, 2009 ; Duncan et al, 2009 ; Goodyer et al, 2009 , 2010 ; Guo and Tillman, 2009 ; Laucht et al, 2009 ; Nilsson et al, 2009 ; Nobile et al, 2009 ; Benjet et al, 2010 ; Brent et al, 2010 ; Mata et al, 2010 ; Nederhof et al, 2010 ; Uddin et al, 2010 , 2011 ; Bouma et al, 2011 ; Hankin et al, 2011 ; Jenness et al, 2011 ; Mata and Gotlib, 2011 ; Thompson et al, 2011 ; Chen et al, 2012 , 2013 ; Petersen et al, 2012 ; Buchmann et al, 2013 ; Bobadilla et al, 2013 ; Comasco et al, 2013 ; Cutuli et al, 2013 ; Kohen et al, 2013 ; Otten and Engels, 2013 ; Oppenheimer et al, 2013 ; Priess-Groben and Hyde, 2013 ; Stavrakakis et al, 2013 ; Banducci et al, 2014 ; Cicchetti and Rogosch, 2014 ; Cruz-Fuentes et al, 2014 ; Little et al, 2014 ; Zhang et al, 2015 ) in adolescents and three studies (Hammen et al, 2010 ; Starr et al, 2013 ; Thompson et al, 2014 ) in young adults were included in this study (Figure 1 ). The 47 studies in adolescence included 20 genes or gene families while the three studies in young adults included three genes (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, one study investigated the BDNF gene plasticity index in adolescents with depressive symptoms without observing any association. Eleven studies (Hilt et al, 2007 ; Duncan et al, 2009 ; Goodyer et al, 2010 ; Mata et al, 2010 ; Chen et al, 2012 , 2013 ; Buchmann et al, 2013 ; Comasco et al, 2013 ; Stavrakakis et al, 2013 ; Cicchetti and Rogosch, 2014 ; Cruz-Fuentes et al, 2014 ) investigated the association between the BDNF Val66Met genotype and adolescent depressive symptoms with only one study showing no association (Nederhof et al, 2010 ; Table 3 ). However, no study analyzed the association between BDNF Val66Met genotype and severity of depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, observa-se que a plasticidade neuronal está intimimente ligada a produção endógena de BDNF (fator neurotrófico derivado do cérebro), que pode ser promovida com atividade física, diminuindo assim também a neuroinflamação e consequentemente prevenindo a obesidade. Em relação ao consumo de ômega 3 e polifenóis e vitaminas do complexo B e Vitamina D, os estudos mostram a relação no metabolismo da gLia e como co-fatores para síntese de neurotransmissores, serotonina, dopamina, GABA, glutamato e melatonina (Guerra et al, 2014, Bot et al, 2020, Cruz-Fuentes et al, 20142017).…”
Section: Figuraunclassified